2016
DOI: 10.1161/jaha.115.002860
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of the Cellular Innate Immune Response During the Process of Human Atherosclerosis

Abstract: BackgroundThe concept of innate immunity is well recognized within the spectrum of atherosclerosis, which is primarily dictated by macrophages. Although current insights to this process are largely based on murine models, there are fundamental differences in the atherosclerotic microenvironment and associated inflammatory response relative to humans. In this light, we characterized the cellular aspects of innate immune response in normal, nonprogressive, and progressive human atherosclerotic plaques.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 61 publications
3
37
0
1
Order By: Relevance
“…In thrombosed coronary atherosclerotic plaques (be they ruptured or eroded), we found only a relatively small number of MCETs and EETs, in line with the usually small number of mast cells and eosinophils, respectively, that have been reported in plaques, including the lesions of MI patients [41,42]. Still, despite their low number, mast cells attract interest because of the role that they play in the process of plaque destabilisation via their release of pro-inflammatory cytokines and vasoactive mediators (histamine, chymase, and tryptase).…”
Section: Mast Cell and Eosinophil Extracellular Traps (Mcets And Eetssupporting
confidence: 84%
“…In thrombosed coronary atherosclerotic plaques (be they ruptured or eroded), we found only a relatively small number of MCETs and EETs, in line with the usually small number of mast cells and eosinophils, respectively, that have been reported in plaques, including the lesions of MI patients [41,42]. Still, despite their low number, mast cells attract interest because of the role that they play in the process of plaque destabilisation via their release of pro-inflammatory cytokines and vasoactive mediators (histamine, chymase, and tryptase).…”
Section: Mast Cell and Eosinophil Extracellular Traps (Mcets And Eetssupporting
confidence: 84%
“…Neutrophils are infiltrating leukocytes present in both mouse and human plaques (van Dijk et al, 2016;van Leeuwen et al, 2008;Zernecke et al, 2008). During human atherosclerosis development, their number significantly increases in the vulnerable lesions (van Dijk et al, 2016).…”
Section: Neutrophilsmentioning
confidence: 99%
“…Though the direct role of eosinophils in atherogenesis remains unclear, clinical studies reveal that absolute eosinophil count, intraplaque eosinophil markers, and eosinophil-specific chemokines are associated with increased risk of CVDs (Haley et al, 2000;Kitano et al, 2017;Lee et al, 2001;Niccoli et al, 2010;Tanaka et al, 2012). While EG2 + eosinophils are considered to be absent during the atherosclerosis development according to immunohistochemistry (IHC) staining of human plaques (van Dijk et al, 2016), the occurrence of eosinophil extracellular trap was identified in human thrombosed atherosclerotic specimen by double staining of eosinophil major basic protein and citrullinated histone H3 (Pertiwi et al, 2019), which might trigger IFN-α production in pDCs. Circulating eosinophils can affect atherogenesis through their cytokine production.…”
Section: Eosinophilsmentioning
confidence: 99%
“…Knee joints from both groups were stained with chromogenic triple-labelling immunohistochemistry (IHC) for M1 and M2 macrophage subsets, based on a previously described method for human tissue 23 . Primary antibodies targeted murine macrophages (F4/80, 1:100, MF48000 (BM8), Invitrogen), M1 macrophages (iNOS, 1:400, ab136918 (K13-A), Abcam) and M2 macrophages (CD206, 1:100, AF2535, R&D Systems).…”
Section: Immunohistochemical Evaluation Of Macrophage Subsets In the mentioning
confidence: 99%